Pedagogical Conditions For Constructive Resolution Of Conflicts In Teacher-Student Relationships - Burieva Nilufar Rasulovna; Joʼrayeva Mashhura Sunnatilla qizi (Euro Asian Journal Publishing, 2024)
This article addresses the pedagogical conditions necessary for the constructive resolution of conflicts in teacher-student relationships. It explores the importance of creating a positive and respectful environment within the educational space, where both teachers and students can engage in open dialogue. The article emphasizes the role of emotional intelligence, communication skills, and conflict resolution strategies in fostering mutual understanding and trust. Key pedagogical approaches include active listening, empathy, and conflict mediation techniques that promote collaboration and problem-solving. The article also highlights the significance of developing a constructive feedback culture and emotional regulation for both teachers and students, which are essential for reducing conflicts and enhancing the overall learning experience.
Keywords: Pedagogical conditions; conflict resolution; emotional intelligence; communication skills